Student adoption and perceptions of the library and information mobile services at the University of Namibia - Nakanduungile, Charlotte Ndeutala (Department of Knowledge and Information Stewardship, 2021)
The aim of the study was to examine students' adoption and perceptions of library and information mobile services at the University of Namibia (UNAM), Main Campus. The research objectives were: to assess factors influencing students' adoption and use of wireless technologies that enable them to access library and information services at UNAM Main Campus; to determine the challenges/opportunities that students face when accessing library and information mobile services at UNAM Main Campus; and to identify students' perceptions of the library and information mobile services offered by UNAM Main Campus library. The study employed a mixed methods approach to gather and analyse data, and was supported by the Diffusion of Innovations theory (DOI). Data were collected from students using a convenience sampling method while purposive sampling was suitable to gather the qualitative data from library staff. Data collection from students was facilitated through a questionnaire, and library staff were interviewed. The study findings showed that mobile phones and laptops have been widely adopted and used by UNAM students. The study concludes that the attributes of innovation (relative advantage, compatibility, complexity, trialability and observability) are considered to be the influencing factors in the adoption and use of wireless technologies that enable students to access library and information services. The study results indicated that students enjoy the benefits which wireless technologies provide such as mobility, flexibility, convenience, engagement and communication in improving learning and academic performance and specifically in accessing library and information mobile services. However, slow network speed/network congestion during peak hours, limited Wi-Fi network coverage in areas and network downtime are some of the challenges that are frequently experienced and frustrate UNAM students when learning and accessing library information services. Though some students are not satisfied with the current provision of library services, and perceived them as inadequate due to limited access, lack of awareness and marketing of mobile services, and lack of a library mobile application, the majority of students perceived library services as adequate due to regular instant interactions and communications via emails, telephones and social networks that they exchange with librarians. The study recommends, among other things, that UNAM library staff be innovative in marketing and creating awareness of information resources and services to attract more students and increase library usage. Since there is no mobile application at vi UNAM library, the study recommends that the library design a mobile application to assist in providing library services to users with mobile devices.